2012
DOI: 10.1099/mic.0.053389-0
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular trafficking and ubiquitination of the Schizosaccharomyces pombe amino acid permease Aat1p

Abstract: In Schizosaccharomyces pombe, neither intracellular sorting nor ubiquitination of amino acid permeases is well understood. In the present study, we show that intracellular sorting of the amino acid permease Aat1p in S. pombe depends on the presence of a nitrogen source in the growth medium. Under nitrogen-sufficient conditions, Aat1p appeared to be stably localized at the Golgi apparatus. In contrast, under nitrogen-insufficient conditions, Aat1p was sorted to the plasma membrane. Over time, plasma membrane-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 58 publications
2
39
0
Order By: Relevance
“…Most newly synthesized transporters are ubiquitylated by the Pub1-Any1 complex at the Golgi when extracellular nutrients are abundant. This ubiquitylation is believed to be necessary for their storage in the Golgi (Nakase et al, 2012) but not for degradation. We would therefore propose that the Pub1-Any1 complex is responsible for storage of the transporters in cells growing under nutrient-rich condition.…”
Section: Role and Regulation Of Pub1-any1 Complexmentioning
confidence: 99%
See 2 more Smart Citations
“…Most newly synthesized transporters are ubiquitylated by the Pub1-Any1 complex at the Golgi when extracellular nutrients are abundant. This ubiquitylation is believed to be necessary for their storage in the Golgi (Nakase et al, 2012) but not for degradation. We would therefore propose that the Pub1-Any1 complex is responsible for storage of the transporters in cells growing under nutrient-rich condition.…”
Section: Role and Regulation Of Pub1-any1 Complexmentioning
confidence: 99%
“…Following a shift to nitrogen-poor medium, Aat1 is transported from the Golgi apparatus to the plasma membrane (PM), followed by endocytosis and transport to the vacuolar lumen (Nakase et al, 2010). Recently, we found that the membrane trafficking of Aat1 was regulated by the ubiquitin ligase Pub1, a homolog of Rsp5 sc , in fission yeast (Nakase et al, 2012). Pub1 to regulates G2/M transition by ubiquitylating Cdc25 (Nefsky and Beach, 1996), which dephosphorylates the inhibitory phosphotyrosine of Cdc2 (Dunphy and Kumagai, 1991;Gautier et al, 1991;Gould and Nurse, 1989;Lundgren et al, 1991;Russell and Nurse, 1986) and cooperates with Flp1/ Clp1 phosphatase (Esteban et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported that Aat1p was ubiquitinated and that ubiquitination is an important determinant of the localization and regulation of the Aat1p in S. pombe. 40) Thus the CUE domain of Vps901p may bind ubiquitinated Aat1p for efficient endocytosis from the plasma membrane to the vacuole. Studies undertaken to confirm this hypothesis should provide a deeper understanding of the role of the CUE domain in fission yeast.…”
Section: Discussionmentioning
confidence: 99%
“…Although the plasma membrane protein(s) responsible for quinidine uptake have not been identified, a general amino acid permease, Aat1p of S. pombe, 14) a homolog of S. cerevisiae Gap1p, might be a site of competition of lysine with quinidine. However, it is also possible that S. pombe Vba2p mediates the uptake of quinidine into the vacuole, like lysine, and enhances the penetration of the quinidine into cells.…”
Section: )mentioning
confidence: 99%